The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.25271/sjuoz.2019.7.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HeaDetermination of Some Heavy Metals in Three Fish Species from Duhok City Markets in Kurdistan of Iraq

Abstract: In this study, the concentrations of some heavy metals including Al, Cu, Fe, Mn, Zn, Cd, Co, Cr, Ni and Pb were determined in the muscles of three commercial fish species available in Duhok city markets in two seasons, using inductively coupled plasmaoptical emission spectrometry (ICP-OES), after the wet digestion process. Lowest and highest mean values of metals in µg/g (dry weight) were as follows: Al: Under Detection Limit (UDL)-3.71, Cu: UDL-4.00, Fe: 5.40-21.44, Mn: UDL-3.45, Zn: 13.38-140.11, while Cd, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Authors from other countries reported different levels of the elements. Lower levels of Cu in canned sardines are reported by authors from Croatia (0.88 mg kg -1 ) [22], Spain (0.513-0.898 mg kg -1 ) [23], Turkey (1.024 mg kg -1 ) [24], Iraq (0.7-2.1 mg kg -1 ) [25], and Nigeria (0.01 mg kg -1 ) [26], but results from USA (0.83 mg kg -1 ) [27], and Brazil (1.31-2.25 mg kg -1 ) [28] are in line with our results. In canned tuna, authors from Spain (0.483 mg kg -1 ) [23], Turkey (0.604 mg kg -1 ) [24], and USA (0.25 mg kg -1 ) [25] found levels lower than ours.…”
Section: Levels Of Copper Zinc and Iron In Canned Fishmentioning
confidence: 74%
See 2 more Smart Citations
“…Authors from other countries reported different levels of the elements. Lower levels of Cu in canned sardines are reported by authors from Croatia (0.88 mg kg -1 ) [22], Spain (0.513-0.898 mg kg -1 ) [23], Turkey (1.024 mg kg -1 ) [24], Iraq (0.7-2.1 mg kg -1 ) [25], and Nigeria (0.01 mg kg -1 ) [26], but results from USA (0.83 mg kg -1 ) [27], and Brazil (1.31-2.25 mg kg -1 ) [28] are in line with our results. In canned tuna, authors from Spain (0.483 mg kg -1 ) [23], Turkey (0.604 mg kg -1 ) [24], and USA (0.25 mg kg -1 ) [25] found levels lower than ours.…”
Section: Levels Of Copper Zinc and Iron In Canned Fishmentioning
confidence: 74%
“…Lower levels of Cu in canned sardines are reported by authors from Croatia (0.88 mg kg -1 ) [22], Spain (0.513-0.898 mg kg -1 ) [23], Turkey (1.024 mg kg -1 ) [24], Iraq (0.7-2.1 mg kg -1 ) [25], and Nigeria (0.01 mg kg -1 ) [26], but results from USA (0.83 mg kg -1 ) [27], and Brazil (1.31-2.25 mg kg -1 ) [28] are in line with our results. In canned tuna, authors from Spain (0.483 mg kg -1 ) [23], Turkey (0.604 mg kg -1 ) [24], and USA (0.25 mg kg -1 ) [25] found levels lower than ours. Reported levels of Zn in canned sardines are higher than ours from Croatia (18 mg kg -1 ) [22], Turkey (23.267 mg kg -1 ) [24], USA (11.45 mg kg -1 ) [27], and Brazil (16.16-36.09 mg kg -1 ) [28], and lower than ours from Spain (4.329-6.767 mg kg -1 ) [23], and Nigeria (0.09-4.49 mg kg -1 ) [26].…”
Section: Levels Of Copper Zinc and Iron In Canned Fishmentioning
confidence: 74%
See 1 more Smart Citation
“…According to the World Health Organization, Iraq recorded increasing in the number of mortality. The numbers of deaths by malignant neoplasm at (2017, 2018 and 2019) were (2738, 21766 and 22737) respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents the popular (TEs) observed in piped drinking water, as well as their sources, WHO recommendations, and possible health hazards [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%